Biodiversity Patterns of Flora and Fauna in Mangrove Ecosystems under Anthropogenic Pressure in South Sumatra, Indonesia - Sarno; Ikhsan, Muhammad; Desitarani; Oktariansyah, Yadi; Pragustiandi, Guntur (Jurnal Sylva Lestari, 2026)
Mangrove habitats serve vital functions; however, this habitat tends to face degradation affected by human activity. This study proposes to evaluate the diversity of flora and fauna in two mangrove habitats in South Sumatra, Indonesia: Banyuasin and Ogan Komering Ilir (OKI). Vegetation analysis was assessed using standard transect and plot-based methods, while fauna were recorded using a rapid assessment method. The results indicated that Banyuasin exhibited a superior flora diversity through a higher Shannon-Wiener Index (H' = 1.61) in contrast to OKI (H' = 1.04); however, the disparity was not statistically significant (p = 0.06). Banyuasin had a greater variety of mangrove trees, including Avicennia alba, Nypa fruticans, Sonneratia caseolaris, Kandelia candel, and Bruguiera gymnorrhiza, than OKI, which only had A. alba and S. caseolaris. In Banyuasin, fauna observations found three mammal species, 17 bird species, and 6 herpetofauna species, compared to one mammal, 16 birds, and 4 herpetofauna in OKI. Species such as Trachypithecus cristatus, Prionailurus sp., and Elanus caeruleus were only found in Banyuasin. These findings conclude that higher human activity in OKI may lead to biodiversity degradation. Therefore,  there is an urgent need for robust conservation policies and community-based management to preserve ecosystem services in the mangrove habitats of these regions. Keywords: biodiversity, conservation, mangrove, rapid assessment, vegetation analysis